2019
DOI: 10.1021/acscatal.9b01051
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Mediated Alcohol Oxidation on Cadmium Sulfide Photocatalysts

Abstract: Developing photocatalysts capable of organic oxidations enables the generation of value-added products from biomass feedstocks through visible light irradiation. Through a series of nonaqueous photocatalytic experiments, we have uncovered that CdS nanowires catalyze benzyl alcohol (BnOH) oxidation and 5-hydroxymethylfufural (HMF) oxidation. The rate can be improved by introducing nitrate salts that act as a redox mediator in solution. Specifically, nitrate salts of lithium, magnesium, calcium, and manganese pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 70 publications
1
43
0
Order By: Relevance
“…Previous work in our lab demonstrates that NO 3 − acts as a redox mediator (i. e. it is regenerated) in photocatalytic PhCH 2 OH oxidation on CdS nanowires . Photoelectrochemically, NO 3 − is not regenerated, representing an EC i mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in our lab demonstrates that NO 3 − acts as a redox mediator (i. e. it is regenerated) in photocatalytic PhCH 2 OH oxidation on CdS nanowires . Photoelectrochemically, NO 3 − is not regenerated, representing an EC i mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a visible‐light excited state of Acr + ‐Mes dye was used to oxidize NO 3 − to NO 3 ⋅ for use as an oxidant in subsequent chemical reactions . Continuing with light‐harvesting examples, our lab demonstrated cooperativity between the NO 3 − /NO 3 ⋅ couple and valence‐band holes on semiconducting CdS nanowires toward indirect alcohol oxidation; this photocatalytic system oxidizes PhCH 2 OH to PhCHO with >99 % selectivity in acetonitrile …”
Section: Introductionmentioning
confidence: 99%
“…For instance, DiMeglio et al. used CdS nanowires as an excellent heterogeneous catalyst and deployed them for conversion of HMF to DFF under benign reaction conditions [67] . High DFF selectivity up to 99 % was obtained assisted by nitrate salts as mediator, which proceeds via a mechanism involving the catalytic generation of a nitrate radical NO 3 .…”
Section: Oxidation Of Hmf Via Innovative Protocolsmentioning
confidence: 99%
“…On a similar note, it has been recently revealed that the presence of redox mediator in the reaction mixture can improve the efficiency of CdS photocatalysts in oxidizing alcohols. DiMeglio and co‐workers [ 129 ] studied the effect of nitrate ions on the selective photocatalytic conversion of benzyl alcohol and 5‐hydroxymethyl furfural. By employing a facile‐hydrothermal method, CdS nanowires were produced and successfully employed to convert benzyl alcohol to benzaldehyde.…”
Section: Catalysts For Selective Oxidation Of Alcoholsmentioning
confidence: 99%
“…However, for a smooth electron transfer, the redox potential of the substrate must be more negative than the VB of the photocatalyst for oxidation reactions or it must be more positive than the CB of the photocatalyst to promote reduction reactions. Since in the case of DiMeglio et al's [ 129 ] work the standard redox potentials of Ca 2+ /Ca (−2.76 eV), Mg 2+ /Mg (−2.37 eV), Li + /Li (−3.05), and Mn 2+ /Mn (−1.18 eV) are all significantly more negative than the CB potential (~ −0.56 eV), these cations cannot react with the photogenerated holes or electrons, thereby having a negligible quenching role on the photocatalytic activity. Additionally, these metal cations can act as a bridge between the benzyl alcohol and CdS surface, causing improved adsorption and LMCT, which could explain the higher conversion rates observed.…”
Section: Catalysts For Selective Oxidation Of Alcoholsmentioning
confidence: 99%